Human peritoneal tight junction, transporter and channel expression in health and kidney failure, and associated solute transport - Levai, Eszter; Marinovic, Iva; Bartosova, Maria; Zhang, Conghui; Schäfer, Betti; Jenei, Hanna; Du, Zhiwei; Drozdz, Dorota; Klaus, Günter; Arbeiter, Klaus; Romero, Philipp; Schwenger, Vedat; et al. (Scientific reports, 2023)
Next to the skin, the peritoneum is the largest human organ, essentially involved in abdominal health and disease states, but information on peritoneal paracellular tight junctions and transcellular channels and transporters relative to peritoneal transmembrane transport is scant. We studied their peritoneal localization and quantity by immunohistochemistry and confocal microscopy in health, in chronic kidney disease (CKD) and on peritoneal dialysis (PD), with the latter allowing for functional characterizations, in a total of 93 individuals (0-75 years). Claudin-1 to -5, and -15, zonula occludens-1, occludin and tricellulin, SGLT1, PiT1/SLC20A1 and ENaC were consistently detected in mesothelial and arteriolar endothelial cells, with age dependent differences for mesothelial claudin-1 and arteriolar claudin-2/3. In CKD mesothelial claudin-1 and arteriolar claudin-2 and -3 were more abundant. Peritonea from PD patients exhibited increased mesothelial and arteriolar claudin-1 and mesothelial claudin-2 abundance and reduced mesothelial and arteriolar claudin-3 and arteriolar ENaC. Transperitoneal creatinine and glucose transport correlated with pore forming arteriolar claudin-2 and mesothelial claudin-4/-15, and creatinine transport with mesothelial sodium/phosphate cotransporter PiT1/SLC20A1. In multivariable analysis, claudin-2 independently predicted the peritoneal transport rates. In conclusion, tight junction, transcellular transporter and channel proteins are consistently expressed in peritoneal mesothelial and endothelial cells with minor variations across age groups, specific modifications by CKD and PD and distinct associations with transperitoneal creatinine and glucose transport rates. The latter deserve experimental studies to demonstrate mechanistic links.